Análise espacial e temporal da esquistossomose mansoni e sua associação com determinantes sociais da saúde no estado de Sergipe, nordeste do Brasil - Jesus, Damyres Menezes Santos de (2020)
Schistosomiasis mansoni is a parasitic disease with wide distribution worldwide. In Brazil, it is a serious public health problem and Sergipe is one of the states with the highest prevalence. Several factors can contribute to its transmission and the Social Determinants of Health (SDH) influence the occurrence of risk factors in the population. It is essential to assess which SDH are associated with the transmission of schistosomiasis in Sergipe, in addition to spatially characterizing the entire state, in order to identify the municipalities that require more attention. The aim of the study was to analyze the positivity rates of schistosomiasis mansoni and its association with social determinants of health in Sergipe, Northeast Brazil. The study is an ecological of time series type with a spatial approach, using the municipalities as the unit of analysis. Epidemiological data were collected from the Schistosomiasis Control Program [Programa de Controle da Esquistossomose (PCE)], from 2008 to 2017. Socioeconomic and environmental variables were collected from the Brazilian Institute of Geography and Statistics [Instituto Brasileiro de Geografia e Estatística (IBGE)], digitally. Descriptive data were tabulated and analyzed in Microsoft Excel 2013. Linear regression analyzes were performed to explain the association of SDH in relation to the positivity of schistosomiasis by the BioEstat program. To calculate the temporal trend, the JoinPoint Regression Program was used. Spatial analysis was performed using the Kernel estimator per centroid and the Moran Global and Local Indices, using the TerraView program. The number of municipalities registered annually varied, with 2011 having the highest number (42) and 2017 having the lowest number (26). 646,088 tests were performed and a total of 54,541 were positive for the presence of the Schistosoma mansoni egg, totaling a positivity of 8.4% in Sergipe. The greatest positivity occurred in 2008 (10.5%) and the lowest in 2014 (6.4%). Most cases had a low intensity of infection (69.1%) and most of the endemic municipalities were found to be in the middle range of positivity (5 to 15%). The temporal analysis of schistosomiasis positivity showed a decreasing trend (APC = -3.68; CI = -6.0 to -1.3; p <0.05). The areas with the highest density of infected people were the coastal region of the state, with the highest concentration in the south. The variables demographic density, MHDI, GDP per capita, illiteracy rate and Gini Index together explained the occurrence of the positivity rate. The Moran Indices showed that all variables analyzed showed positive spatial autocorrelation, except for households with sewage, GDP per capita and rural population. The malacological investigation was not recorded regularly and only nine municipalities provided information. There were records of Biomphalaria glabrata and B. straminea in the state, the majority of the first specie. Therefore, Sergipe showed a high rate of positivity, with a decreasing trend and positive spatial autocorrelation, and there are DSS associated with schistosomiasis, which should be analyzed for prevention strategies.